Implementasi Kompetensi Sosial Guru PAK dalam Manajemen Disiplin Kelas di UPTD SDN 070988 Hilinakhe - Wilhana Jasephin Zebua (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the implementation of social competence of Christian Religious Education (PAK) teachers in disciplining students at UPTD SD Negeri 070988 Hilinakhe, Gunungsitoli City. The social competence of PAK teachers has an important role in creating harmonious relationships between teachers, students, and parents, which can support the creation of discipline in the school environment. This study uses a qualitative approach by exploring library sources to describe how PAK teachers apply social competence in disciplining students. Data were collected through in-depth interviews with PAK teachers, direct observation in class, and analysis of documents related to discipline policies implemented in schools. The results of the study indicate that PAK teachers at UPTD SD Negeri 070988 Hilinakhe have implemented their social competence in an effective way, through good communication with students, providing moral and spiritual examples. The conclusion in this study shows that the implementation of consistent discipline strategies for the diversity of student backgrounds is greatly influenced by the social competence of teachers through good communication. In addition, there is closer cooperation between the school, students, and parents to strengthen the implementation of discipline in the school environment.